Development Strategy of Yellow Tail Fusilier Fish (Caesio cuning) Resources Management on Coral Ecosystem in The Seribu Islands - Neviaty P Zamani; Yusli Wardiatno; Raimundus Nggajo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Population of Yellow tail fusilier fish (Caesio cuning) in Seribu Islands at this time has decreased. The main cause of decreasing in abundance of the fish is due to degradation of coral reef ecosystem as a habitat of the fish. The purposes  of the study is  to examine the association of  Yellow tail fusilier fish resources with habitat characteristics. The study was conducted in the Seribu Islands waters on May 2009, at the four islands, each consisting of two observation locations. Percentage benthic  substrate cover, and the number of coral lifeform using the Square Transect method, while to see the abundance of the fish resources using Underwater Visual Cencus. Benthic substrate cover was dominated by abiotic cover (36.42%), hard coral cover was in fair condition (32.27%), dominated by foliose coral, massive coral, acropora branching and encrusting coral. The abundance of Yellow tail fusilier fish was 67 individu/250 m2. North Pramuka, West Panggang, and South Panggang was only observed some small fishes. Closing area can be implemented for management purposes with the combination of introducing brooder.  In vise versa East Pramuka and East Kayu Angin have been observed only adult fishes. Closing area can be implemented for management purposes with the combination of introducing juveniles. In West Kayu Angin closing area can be implemented to give the opportunity juvenile for growing and adult for breading.  South Belanda have all range of size fishes as well as good condition of habitat. It is therefore, this can be developed as marine protected area with eco-freienly marine tourism activities. Keywords: coral reef ecosystem, fish resources, yellow tail fusilier fish, habitat linkages, Seribu islands.